PENGARUH LINGKUNGAN KERJA DAN BEBAN KERJA TERHADAP TURNOVER INTENTION DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MODERASI (STUDI KASUS DI PT. SUMBER SAWIT MAKMUR UNIT BANDAR PULAU) - Prabowo, Aji; Khair, Hazmanan; Sabrina, R (JURNAL ILMU MANAJEMEN DAN KEWIRAUSAHAAN (JIMK), 2024)
This study aims to determine and analyze the effect of work environment and workload on turnover intention with job satisfaction as moderation. The object of research was conducted at PT Sumber Sawit Makmur Unit Bandar Pulau, Bandar Pulau District, Asahan Regency. This research is included in the category of causal research using a quantitative approach. Sampling using the Slovin Formula which amounted to 53 field employees from a population of 113 people. Data collection techniques are carried out by means of observation, interviews, distributing questionnaires and documentation studies. This research analyzes using the help of Smart PLS (Partial Least Square) software version 3.0 which is applied with computer media to test the strength of the relationship between turnover intention and its independent variables, namely work environment and workload and job satisfaction as moderating variables. The results of this study prove that the work environment has a negative and insignificant effect on turnover intention.Workload has a positive and insignificant effect on turnover intention.Job satisfaction variables are not able to moderate the influence of work environment and workload on turnover intention.